Onshore unconventional hydrocarbon development : induced seismicity and innovations in managing risk-day 2 : proceedings of a workshop - Eide, Elizabeth A. (The National Academies Press, 2018)
"Oil and gas well completion and stimulation technologies to develop unconventional hydrocarbon resources in the United States have evolved over the past several decades, particularly in relation to the development of shale oil and shale gas. Shale oil and shale gas resources and the technology associated with their production are often termed "unconventional" because the oil and gas trapped inside the shale or other low-permeability rock formation cannot be extracted using conventional technologies. Since about 2005, the application of these technologies to fields in the U.S. have helped produce natural gas and oil in volumes that allowed the country to reduce its crude oil imports by more than 50% and to become a net natural gas exporter. The regional and national economic and energy advances gained through production and use of these resources have been accompanied, however, by rapid expansion of the infrastructure associated with the development of these fields and public concern over the impacts to surface- and groundwater, air, land, and communities where the resources are extracted. A workshop on December 1 and 2, 2016 at the National Academy of Sciences in Washington, DC, explored the management of risk related to the development of onshore unconventional oil and gas resources such as shale oil and shale gas. The second part of the workshop, on December 2, addressed issues associated with induced seismicity and managing the risk of induced seismic events associated with development of oil and gas fields. This publication summarizes the presentations and discussions from this second day of the workshop"--Publisher's description